Primary characteristics of the extreme heavy rainfall event over Henan in July 2021. (23rd September 2022) - Sun, Jianhua; Fu, Shenming; Wang, Huijie; Zhang, Yuanchun; Chen, Yun; Su, Aifang; Wang, Yaqiang; Tang, Huan; Ma, Ruoyun
Abstract: During mid‐July 2021, an extreme heavy rainfall event (HRE) occurred in Henan Province (hereafter "21.7" HRE), with extreme hourly precipitation of 201.9 mm appearing at Zhengzhou station. Our preliminary analyses of the "21.7" HRE using the observations and ECMWF (European Centre for Medium‐Range Weather Forecasts) ERA5 reanalysis data, reached the following conclusions. Favorable configurations of various synoptic weather systems (e.g., strong upper‐level high‐pressure ridge, intense middle‐level low‐pressure trough) acted as crucial background conditions for the occurrence of the "21.7" HRE. A 21‐h long‐lived mesoscale convective vortex (MCV), mainly located in the middle and lower troposphere west of Zhengzhou city, was a key system that produced the extreme hourly rainfall of 201.9 mm·h −1 . The MCV's development/sustainment was dominated by the vertical transport of cyclonic vorticity and tilting, as well as the horizontal import of cyclonic vorticity to the vortex's key region. In contrast, the divergence‐related vertical shrinking was the most detrimental factor. Lagrangian moisture transport analysis showed that moisture for the extreme heavy rainfall in Zhengzhou on July 20 mainly came from levels below 2200 m, driven by airflows on the peripheries of tropical cyclones IN‐FA and CEMPAKA. To enhance the understanding of "21.7" HRE, we suggest more in‐depth investigations in the future. Abstract : China is located in the East Asian monsoon region, which experiences relatively frequent heavy rainfall events in summer. Generally, the heavy rainfall frequency and accumulated amount in South China are higher than those of North China, whereas, the intensity of heavy rainfall in North China is similar to or even higher than that of South China. In July 2021, a record‐breaking heavy rainfall event occurred in Henan Province. The maximum observed precipitation in the whole event exceeded 1000 m, and an extreme hourly rainfall of 201.9 mm occurred in Zhengzhou. The major favorable large‐scale circulation conducive to heavy rainfall in North China during this event includes an extratropical‐cyclone/low‐pressure area between the continental high pressure and intensive subtropical high. The moisture related to two tropical cyclones IN‐FA and CEMPAKA was transported from the Western Pacific and the South China Sea to Henan Province. A mesoscale convective vortex was a key system to produce the extreme hourly rainfall of 201.9 mm in Zhengzhou city on 20 July, 2022.